Beethoven Haus (Fischer Haus) - Appelrath, L. (artist):::Creator::::::::::::
Engraving of the Fischer Haus in Bonn, Germany, incorrectly labelled as "Beethovens Geburtshaus"; color version of the image published in the Neue Illustrirte Zeitung (2 May 1880, p. 539).